Exercise training improved blood flow velocity and autonomic nervous activity - Noor Azmi, Azran Azhim; M., Katai; M., Akutagawa; Y., Hirao; K., Yoshizaki; S., Obara; M., Nomura; H., Tanaka; H., Yamaguchi; Y., Kinouchi (IEEE, 2006)
The present study aimed to investigate non-invasively the effects of a short-term 4 week aerobic training program on the resting common carotid artery (CCA) blood flow velocity waveforms and autonomic nervous activity in young sedentary healthy subjects. It was hypothesis that training-induced the enhancement of blood flow is associated with the improvement of autonomic nervous function. The CCA blood velocities were measured for 3 minutes at resting sitting posture with synchronized measurement of electrocardiogram (ECG) and brachial blood pressure (BP). Autonomic activity was assessed by low frequency (LF) power, as an index of sympathetic activity and high frequency (HF) power, as an index of parasympathetic activity obtained from power spectral of RR intervals. Training exercise-induced the significant enhancement of all blood velocity waveforms is associated with decreasing of heart rate at rest. The evidence of improvement in training was reinforced by a significant reduction in peripheral vascular resistance and increase in heart rate variability (HRV) and HF power of HRV analysis, an index of vagal tone or parasympathetic activity. However, systolic (SBP), diastolic (DBP) and its mean blood pressure (MBP) are not significantly changed with the training. We conclude that short-term aerobic exercise training could improve cardiovascular and autonomic nervous system functions in the sedentary young men. With the further study, training effect may be simply evaluated using the non-invasive measurement system of blood velocities in CCA.